Experimental investigation of structural and radiation shielding features of Li2O-BaO-ZnO-B2O3-Bi2O3 glass systems - Sayyed, M.I.; Mhareb, M.H.A.; Şakar, Betül Ceviz; Mahmoud, K.A.; Şakar, Erdem; Abdurabu Thabit, Hammam; Kaky, Kawa M.; Baki, S.O. (Elsevier, 2024)
To investigate the effects of increasing the amount of Bi2O3 in the glass composition, a novel glass system was created with the following chemical composition: 5Li2O-5BaO-10ZnO-(30-x) B2O3-(50+x) Bi2O3. x = 10, 15, 20 mol%. A micro-Raman spectrometer (WITec alpha300 R) was utilized to demonstrate the change in chemical bonds brought on by the addition of Bi2O3. Additionally, the Makishema-Makinze theory was employed to calculate the manufactured glasses' mechanical properties. According to the theoretical analysis of mechanical properties, switching from B2O3 to the compound Bi2O3 results in a decrease in elastic moduli, packing density, and hardness. Additionally, the gamma-ray shielding properties were evaluated experimentally using a high purity germanium detector and affirmed using the Monte Carlo simulation. The analysis showed that raising the Bi2O3 content from 60 to 70 mol% resulted in a linear attenuation coefficient enhancment by 12.4% (at 0.059 MeV), 12% (at 0.662 MeV), and 10% (at 2.506 MeV).